The Influence of Profability, Transfer Pricing, and Capital Intensity on Tax Avoidance in Making Companies in Property and Real Estate Sub Sectors Listed on the Indonesia Stock Exchange, 2017-2021 - Nurwati Nurwati; Febri Nurlita; Maciejewski Valeria (Yayasan Adra Karima Hubbi, 2023)
This research aims to determine whether there is an effect of profitability, transfer pricing and capital intensity with tax avoidance as the control variable both simultaneously and partially. This study listed the Property and Real Estate sub-sector companies on the Indonesia Stock Exchange in 2017-2021, with a sample of 8 companies taken by purposive sampling. The research variables consist of independent variables: Profitability, Transfer Pricing, and Capital Intensity—research method aims to determine the relationship between two variables, one with another variable. The data used is secondary data. The collected data were analyzed using the SPSS Statistics 25 program. The results showed that only Profitability, Transfer Pricing, and Capital Intensity significantly affected the tax avoidance prediction. In contrast, companies did not have a significant effect on the prediction of tax avoidance.